Effects of the hydraulic infrastructure on economic growth: evidence from Catalonia - Jaume Freire-González; Ignasi Puig-Ventosa (Sustainable Water Resources Management, 2016)
Public infrastructures have a positive effect on labour productivity and growth. However, different types of infrastructure produce different magnitudes of effects. This article contains an analysis of the stock of hydraulic capital and investments in Catalonia and provides empirical evidence of its effect on productivity and growth. It also compares the magnitude of this effect with the magnitude of other types of public and private capital. The research shows that hydraulic capital and investments have a positive and significant effect on economic growth. However, this effect may be lower than that resulting from other forms of public or private capital.
Keywords: 330